1996
DOI: 10.1021/cm950609c
|View full text |Cite
|
Sign up to set email alerts
|

General Route to Nanocrystalline Oxides by Hydrodynamic Cavitation

Abstract: We have developed the WPI cavitational materials process for the production of phasepure, nanostructured materials. Hydrodynamic cavitation is generated mechanically using a high-pressure fluid system. The method begins with a precipitant stream that experiences a large pressure drop (21 000 psi ambient) across a patented geometry interaction chamber. Due to the large pressure drop, bubbles are formed and collapse, causing localized heating of the solvent. In addition, the precipitate undergoes a high degree o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 18 publications
0
18
0
Order By: Relevance
“…Sunstrom et al [16] reported a similar XRD pattern for TiO 2 prepared by the hydrodynamic cavitation method. The particle size calculations were found to be around 5-17 nm.…”
Section: Resultsmentioning
confidence: 73%
“…Sunstrom et al [16] reported a similar XRD pattern for TiO 2 prepared by the hydrodynamic cavitation method. The particle size calculations were found to be around 5-17 nm.…”
Section: Resultsmentioning
confidence: 73%
“…In hydrodynamic cavitation processing, nanoparticles are generated through the formation and release of gas bubbles within the sol-gel solution that is rapidly pressurized within a supercritical drying chamber and exposed to cavitational disturbances and high temperature heating [52]. The erupted hydrodynamic bubbles are responsible for nucleation, growth, and quenching of the nanoparticles with the particle size controlled by adjusting the pressure and the solution retention time in the cavitation chamber.…”
Section: Resultsmentioning
confidence: 99%
“…Although light emission from hydrodynamic cavitations was observed in the 1960's [4], the chemical effects of hydrodynamic cavitation have only been properly investigated since 1993 [5][6][7][8][9]. Hydrodynamic cavitation has been recently employed in the preparation of nanostructured materials [10,11], the removal of chemicals from wastewater treatment [12][13][14][15][16][17][18][19], water disinfection [20], and the degradation of polymers [21,22].Chlorocarbons consist of chloromethane, dichloromethane, chloroform, carbon tetrachloride, trichloroethylene, tetrachloroethylene, and 1,1,1-trichloroethane. Carbon tetrachloride and chloroform are among the most widespread contaminants in surface and underground water, and in tap water treated by chlorination.…”
mentioning
confidence: 99%
“…The efficacy of hydrodynamic cavitation reactors has been conclusively shown to be better than ultrasonic bath reactors [8,9,29]. However, earlier investigations on the chemical effects of hydrodynamic cavitation were carried out at very high upstream pressure (10-150 MPa) [7,10] or at pilot-plant scale (50-100 L) [29,30]. In this investigation, chloroform and carbon tetrachloride were destructed at quite low upstream pressure (0.1-0.7 MPa) within a labscale circulating reactor (2.4 L).…”
mentioning
confidence: 99%